Eficácia da drenagem linfática mecânica no tratamento do linfedema pós-mastectomia - Bordin Junior, Newton Antonio (2012)
Although lymphedema resulting from the treatment of breast cancer is secondary lymphedema, it follows the same diagnostic and treatment criteria as other types of lymphedema. Its prevalence varies from 7% to more than 50% of patients submitted to surgery depending on the surgical approach and associated treatment employed. Main: objectives of this study were to evaluate the efficacy of mechanical lymphatic drainage in reducing the volume of lymphedematous limbs after breast cancer treatment and identify the optimal time of treatment. Patients and Method: From July 2007 to July 2008, twenty-five patients with lymphedema resulting from breast cancer treatment were enrolled in this study by order of arrival at the Godoy Clinic. The ages of the patients ranged from 42 to 86 years old (mean: 55.6 years). Diagnosis of lymphoedema was made clinically and confirmed by volumetry. Lymphedema was confirmed with a difference in volume between the patient s arms of more than 200 ml. Exclusion criteria were the presence of active infection, joint problems including immobility due to neurological involvement or any clinical condition in which physical exercises are contraindicated, such as heart failure and advanced active cancer. This study was divided into two stages with all patients being evaluated by water-displacement volumetry before and after activities. In phase I (n = 25) the patients were submitted to one hour of activities and phase II (n = 13) patients were submitted to three hours of activities with volumetry being carried out every hour. The RAGodoy® electromechanical device, which makes 15 to 25 passive flexion and extension movements of the elbow joint per minute, was used for mechanical lymphatic drainage. The t-test with a Bonferroni alpha correction of 0.008 was used for statistical analysis and an alpha error of 5% (p-value ≤ 0.05) was considered significant. The study was approved by the Research Ethics Committee of the Medical School in Sao Jose do Rio Preto. Results: The reduction in volume was significant in Phase I (one hour treatment: p < 0.001), with the initial mean weight being 2026.4 and final weight being 1967.2 (mean loss of 59.2 grams). In Phase II (three hours activities), the reductions were significant in the first and second hours (p <0.0005 and 0.002, respectively). However, no statically significant difference was seen using a Bonferroni alpha correction of 0.008 (p-value = 0.01) between the second and third hour. Conclusion: In conclusion the use of the device reduces the volume of lymphedematous limbs; it is most effective in the first hour, but provides significant reductions for a maximum of two hours.